PATTERN OF INJURIES IN COUNTER TERRORISM OPERATIONS: AN EXPERIENCE AT A TERTIARY CARE HOSPITAL - Butt, Muhammad Qasim; Chatha, Sohail Saqib; Ghumman, Adeel Qamar; Farooq, Mahwish (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the pattern of injuries sustained by military persons in counterterrorism operations.Study Design: Descriptive study with retrospective data collection.Place and Duration of Study: The study was carried out at Combined Military Hospital (CMH) Kohat over a period of four years from December 2008 to December 2012.Material and Methods: Data of patients was collected by noting the injuries suffered by soldiers and officers evacuated from operational area and their outcome after treatment in tertiary care hospital from hospital papers.Results: Total of 1226 patients were received from operational area over a period of 4 years from December 2008 to December 2012. One hundred and fifty seven (12.8%) were brought in dead while 1069 (87.2%) were received alive. Twelve (0.98%) patients died during hospital treatment. All patients were male. A total of 593 (48.4%) suffered limb injuries, 50 (4.1%) suffered neck injuries, 61(5%) had chest injuries, 30 (2.4%) suffered head injuries, 62 (5%) presented with abdominal injuries, 52 (4.3%) suffered eye and face injuries, 3 (0.2%) suffered acoustic trauma, 9 (0.7%) had vascular injuries while 366 (29.8%) suffered multiple injuries. In 480 (39.2%) patients mechanism of injury was fire arm injuries, 34 (2.8%) suffered road traffic accidents while in 712 (58.1%) injury was caused by Improvised Explosive Device.Conclusion: There is a shift in the pattern of injuries in modern warfare therefore necessary training of medical staff is required along with speedy evacuation of patients to tertiary care hospitals.